Mechanical and Flame Retardant Properties and Microstructure of Expandable Graphite/Silicone Rubber Composites. Issue 2 (1st February 2016) - Hong, Ling; Hu, Xiaoxian
ABSTRACT: Flame-retardant expandable graphite (EG)/silicone rubber (SR) composites were prepared using nano-CaCO3 particles as reinforcement filler. In addition to mechanical measurements, limited oxygen index (LOI), UL-94 and cone calorimeter tests (CCT), the thermal properties were tested by thermogravimetric analysis (TGA). The results showed that the content and particle size of the EG both had large effects on the flammability and mechanical properties of the EG/SR blends. The composites that contained 25 phr EG (50–80 mu) had excellent LOI values, 47–48, and achieved the UL-94 V-0 level while the pure SR sample had the LOI value of 25 and achieved the UL-94 V-2 level. The data obtained from the CCT indicated that the addition of EG decreased remarkably the heat release rate, smoke emission, and mass loss rate of the composites. SEM microphotographs of the EG/SR composites before and after combustion demonstrated that EG underwent a large volume expansion, and the multiporous char structure blocked heat transfer and protected the substrate from fire.